Structure and functioning of oil cavities in the shoot apex of Metrodorea nigra A. St.-Hil. (Rutaceae) - Machado, Silvia Rodrigues [UNESP]; Canaveze, Yve [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Springer Nature, 2017)
This study investigates the histology and subcellular features of secretory cavities during the development of the shoot apex of Metrodorea nigra A. St.-Hil. in order to better understand the functioning of these glands. This Rutaceae species is a very suitable model for studying secretory cavity life span, since the shoot apex exhibits both dormant and growth stages during its annual cycle. Shoot apices were collected during the dormant and growth stages from populations of M. nigra growing under natural conditions. Materials were processed using standard techniques for light and electron microscopy. The secretory cavities originate under the protodermis, and their initiation is restricted to the early developmental stage of shoot organs, which are protected by a hood-shaped structure. Secretory cavities have a multi-seriate epithelium surrounding a lumen that expands schizolysigenously. Oil production begins before lumen formation. When the shoot apex resumes development after the dormant stage, the glands remain active in oil secretion in the developing shoot apex and fully expanded leaves. The mature epithelial cells are flattened and exhibit very thin walls, large oil bodies, leucoplasts surrounded by endoplasmic reticulum, and mitochondria with unusual morphology. The tangential walls of the epithelial cells facing the lumen undergo continuous peeling. The vacuole extrusion appears to be the primary mode of release oil into the lumen, in an exocytotic way. The continuity of oil secretion is ensured by the replacement of the damaged inner epithelial cells by divisions in the parenchyma layer that surround the oil gland, likely a meristematic sheath.
Keywords: Bud dormancy; Essential oil; Metrodorea nigra; Open growth; Secretory cavity; Ultrastructure